THE ENHANCEMENT OF UNDERSTANDING CONCEPT OF FORCE THROUGH PREDICT OBSERVE EXPLAIN (POE) MODEL - Lelyta Anggraeny; Peduk Rintayati; Muhammad Shaifuddin (Universitas Sebelas Maret, 2018)
The purpose of this research was to improve understanding of the concept of force through Predict Observe Explain (POE) Model to the students in grade IV of State Primary School 1 of Munggung Surakarta in Academic Year 2017/2018. The form of this research was a Classroom Action Research which conducted in two cycles. Each cycle consisted of four stages i.e. planning, action, observation, and reflection. The subjects of this research included teacher and students as many as 20 in Grade IV of the aforementioned school in Academic Year 2017/2018. The data collected by interview, observation, test, and documentation techniques. The data validity test were using content validity, triangulation of resource, and triangulation of technique.The result of this research shows that in each cycle there is an improvement in the conceptual understanding values from pre-action, cycle I until cycle II.